Factors affecting job interview communication competence of unemployed graduates in Malaysia / Masturah Alias - Alias, Masturah (Institute of Graduate Studies, UiTM, 2015)
One of the challenges that graduates faced at job interviews is their inability to communicate competently in English, the language most often used especially at the multinational companies and government-linked companies (GLCs) job interviews. This inability to communicate competently at job interviews is one of the reasons of unemployment among graduates. This study aimed to determine the factors affecting job interview communication competence of unemployed graduates in Malaysia. The present study employed the mixed method research design using questionnaires followed by a semi structured interview with thirteen respondents. The population sample comprised unemployed graduates participating in the SL1M program (Skim Latihan 1 Malaysia) launched by the government to address the unemployment problem among Malaysian graduates. Questionnaires were distributed to 506 unemployed graduates at three participating GLCs in the Klang Valley of which a total of 337 questionnaires were finally used for data analyses. The Job Interview Communication Competence Scale (quantitative instrument) consisted of items on the five factors of communication competence and also those of the dependent variable job interview communication competence. Overall, findings revealed moderate to low levels of general communication skills, context knowledge, English language knowledge and attitude towards the use of English language…